Identifying success factors of Mamak restaurants in Malaysia - Othman, Mohhidin; Abu Bakar, Ainul Zakiah; Kandasamy, Tachaini; Chua, Bee Lia (Science Publishing Corporation, 2018)
The foodservice industry is among one of the largest industries that contribute significantly to Malaysia's economic growth. The restaurant businesses are operating as a highly competitive market as many food operators are competing with each other in attracting customers. Mamak restaurant is one of the well-established ethnic-based restaurants in Malaysia which is usually seen fully packed with customers most of the time. Despite, the popularity of Mamak restaurant has been acknowledged in many previous studies, there is no attempt done to explore factors that enable the Mamak restaurant to be successful. Therefore, this paper intended to explore success factors of Mamak restaurant in Malaysia based on the customers' perspective and the managerial practices of the Mamak restaurant operators. This paper also aimed to create a business model of success factors of the Mamak restaurant which could be a benchmark by prospective restauranteurs and researchers. The data was collected using an in-depth interview with customers and restaurant operators based on a purposive sampling. The huge data transcription was analyzed in detail to classify codes and categories that summarize and describe the success factors of Mamak restaurant. This study found that location, environment, product, facilities, service, and price of Mamak restaurant have positively contributed to the success of Mamak restaurants. Thus, other food operators can emulate the strategies and practices of Mamak restaurants' management to maximize the potential of their restaurant business.